Laser spectroscopy on volatile sulfur compounds: possibilities for breath analysis. - Ciaffoni, L; Peverall, R; Ritchie, G (2011)
There is an emerging interest in the detection of volatile sulfur compounds (VSCs) in the breath environment, given their biological relevance as potential signatures of several pathological conditions. Particularly, laser-based spectroscopic sensors are candidates for conducting accurate breath diagnostics in clinical settings. With these aims in mind, the current status of VSC sensing via laser absorption spectroscopy is reviewed in this paper. Attention has been focused on the most promising exhaled markers of pathological conditions, namely hydrogen sulfide, carbonyl sulfide, methanethiol, carbon disulfide and dimethyl sulfide. Details of the most relevant spectroscopic studies conducted on such molecules are presented, together with suggestions on the future direction of this challenging analytical field.